A survey on timeliness of quarterly reports by Malaysian listed companies - Ibrahim, Idawati; Ayoup, Hazeline; Che Ahmad, Ayoib (Universiti Utara Malaysia, 2004)
Interim report provides financial information for a period shorter than the companies financial year period. As interim report was mandated by KLSE to be produced every quarter of the business cycle, the timeliness of the reports is very crucial to ensure that the information is timely and relevant to the investors in making their economic decisions. The objectives of this research are examine the timeliness of interim report and to analyses the level compliance as required by KLSE Listing Requirements. In addition, this research also investigates whether listed companies voluntarily purchase audit services for the interim reports as they might add value to examined. Finally, this study investigates the enforcement actions by KLSE for late submission of quarterly reports and provides evidence on the practice of interim reporting among listed companies in Malaysia.This study used a sample of interim reports from companies listed on main board of Kuala Lumpur Stock Exchange for 2002. The sample was selected by using disproportionate stratified random sampling.The descriptive and uni variate analyses are provided. Results of the study shows that only 2.8% of the interim reports scrutinized were not submitted within two month period as required by KLSE. The average lag taken by companies to prepare and submit their interim reports were 54 days.